1990
DOI: 10.1088/0022-3727/23/4/004
|View full text |Cite
|
Sign up to set email alerts
|

Electron energy distribution and transport coefficients of electron swarms in SF6and nitrogen mixtures

Abstract: Electron swarm behaviour in SF6 and nitrogen mixtures is analysed over the E/N range from 141 to 707 Td by a three-term Boltzmann equation method. A set of electron collision cross sections, which was determined consistently with measurements for the respective pure gases by the authors ((SF,, ltoh et a/ (1988); N2, Ohmori et a/ (1988)), is used. The calculation is carried out for the steady-state Townsend (SST), pulsed Townsend (PT) and time-of-flight (TOF) experiments. In particular the TOF parameters of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
13
1

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 20 publications
(11 reference statements)
3
13
1
Order By: Relevance
“…At lower E / N , as the SF6 content of the mixture increases, the mean energies increase while at high E / N values the tendency reverses. Similar behavior of the mean energies in SFs+Nz mixtures has been observed recently in a three-term Boltsmann equation method[7].4. CONCLUSIONSH E limiting E / N values in SFs+Nz mixtures are eval-T uated directly by a Monte Carlo simulation technique rather than deducing these values from the plots of effective ionieation coefficients as a function of E / N .…”
supporting
confidence: 84%
See 1 more Smart Citation
“…At lower E / N , as the SF6 content of the mixture increases, the mean energies increase while at high E / N values the tendency reverses. Similar behavior of the mean energies in SFs+Nz mixtures has been observed recently in a three-term Boltsmann equation method[7].4. CONCLUSIONSH E limiting E / N values in SFs+Nz mixtures are eval-T uated directly by a Monte Carlo simulation technique rather than deducing these values from the plots of effective ionieation coefficients as a function of E / N .…”
supporting
confidence: 84%
“…Therefore, (E/N)l;,,, is an important parameter to predict the electrical insulation characteristics in electronegative gas or gas mixtures. However, this parameter is usually deduced from the graphs of the variation of the effective ionization coefficient d with respect to E / N at a given mixture ratio [7,8], although ? ?Boltzmann-type calculations can be used to obtain the limiting field value numerically.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies of gas dielectric breakdown properties have concentrated on room temperature values. [13][14][15][16] For these reasons, it is important to study and better understand the dielectric properties of hot gas mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…SF is an electronegative gas, and possesses very high dielectric strength, but its GWP is much higher than that of 2 CO , so it has been listed as one of the restricted gases in Kyoto protocol signed in 1997. Some researches indicated that when 2 N , 2 CO and air are added into 6 SF , the mixtures electric strength are comparable to that of 6 SF , their GWP are much little, and the feasibility had been proved by many experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Some researches indicated that when 2 N , 2 CO and air are added into 6 SF , the mixtures electric strength are comparable to that of 6 SF , their GWP are much little, and the feasibility had been proved by many experiments. Among of them, 6 2 / SF N mixtures had been used in industry preliminary [1].…”
Section: Introductionmentioning
confidence: 99%